2020
DOI: 10.26421/qic20.11-12-4
|View full text |Cite
|
Sign up to set email alerts
|

A thermal quantum classifier

Abstract: We find that the additivity of quantum information channels enables one to introduce a quantum classifier or a quantum decision maker. Proper measurement and sensing of temperature are of central importance to the realization of nanoscale quantum devices. Minimal classifiers may constitute the basic units for the physical quantum neural networks. We introduce a binary temperature classifier quantum model that operates in a thermal environment. In the present study, first the mathematical model was introduced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The physics we use in this model is based on the complete positivity, additivity [19] and divisibility [20,21] of quantum dynamical maps. As has been done in previous studies [7], [22], superconducting circuits can be shown as a physical model to apply the theoretical model with possible defects. We leave the activation and training tasks out of the scope of this study for our proposed classifier.…”
Section: Introductionmentioning
confidence: 97%
“…The physics we use in this model is based on the complete positivity, additivity [19] and divisibility [20,21] of quantum dynamical maps. As has been done in previous studies [7], [22], superconducting circuits can be shown as a physical model to apply the theoretical model with possible defects. We leave the activation and training tasks out of the scope of this study for our proposed classifier.…”
Section: Introductionmentioning
confidence: 97%
“…One example is Korkmaz et al, who propose a scheme where the system is coupled to thermal reservoirs. The input data is encoded in these reservoirs and it is possible to show that this system works as a natural classifier that resembles the perceptron from Rosenblatt [12,13]. As done by Korkmaz et al, investigating options of open quantum algorithms for machine learning is one alternative to work around the limitations of the difference between the expected behavior versus the actual behavior of quantum computing.…”
Section: Introductionmentioning
confidence: 99%